Modeling heart failure by induced pluripotent stem cell-derived organoids - Bissoli, Irene; Alabiso, Francesco; Cosentino, Cristina; Seragnoli Chystyakova, Aleksandra; Ferré, Fabrizio; Alviano, Francesco; Marrazzo, Pasquale; Pignatti, Carla; Agnetti, Giulio; Regazzi, Romano; Flamigni, Flavio; D’Adamo, Stefania; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2025)
Cardiac organoids offer significant advantages for in vitro studies, as their 3D structure and cellular composition more closely replicate tissue complexity compared to 2D models. This is particularly relevant for studying complex diseases like heart failure (HF), which involve multiple cell types and cardiac structures. Thus, the primary aim of this study was to produce self-assembled, scaffold-free cardiac organoids from induced pluripotent stem cells (iPSCs), capable of simulating key aspects of HF in vitro. Gene expression analysis confirmed a transition from stemness markers (OCT4, NANOG) to cardiac markers (TNNT2, DES), validating their cardiac phenotype. To induce hallmark HF features, endothelin-1 (ET-1) treatment was applied. Key findings indicate that this experimental model successfully reproduced HF pathological markers, including the upregulation of genes encoding atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), and the cytoskeletal protein α-skeletal actin (ACTA1), along with changes in microRNA (miR) expression profiles. Functionally, ET-1 treatment reduced organoid contractility, indicating a decline in contractile function—a hallmark of HF. Furthermore, histological analyses by Thioflavin T (ThT) staining, ThT fluorescence assay and filter trap assay on protein extracts demonstrated protein aggregation following ET-1 treatment. Co-administration of various nutraceuticals was shown to mitigate these effects. These findings underscore the value of this ET-1-stimulated cardiac organoid model as a powerful platform for studying HF mechanisms and evaluating novel therapeutic approaches. •Self-assembling iPSC-derived organoids can be stimulated by ET-1 to express markers of HF, such as ANP, BNP, and ACTA1.•The microRNA profiling after stimulation with ET-1 is significantly changed.•Protein aggregation can be triggered by ET-1 in this kind of HF model.•These findings support the use of this model to investigate in vitro mechanisms of HF and the effects of new treatments.